Time trends in schoolwork pressure among Dutch adolescents, 2001-2017: Gender and educational differences - Cosma, Alina; Stevens, Gonneke W J M; Vollebergh, Wilma A M; De Looze, Margreet (Scandinavian journal of public health, 2022)
AIMS: This study investigated gender and educational differences in trends in schoolwork pressure between 2001 and 2017 in nationally representative samples of Dutch adolescents in secondary education. METHODS: Data from five surveys of the Dutch Health Behaviour in School-aged Children study were used. RESULTS: Across the surveys, an increase in perceived schoolwork pressure was observed. Girls and adolescents enrolled in the higher educational levels reported higher levels of perceived schoolwork pressure and the strongest increase in schoolwork pressure over time. Especially for girls, there was a stronger increase in schoolwork pressure for those enrolled in higher educational tracks. CONCLUSIONS: Increases in schoolwork pressure over time were stronger among Dutch girls and students in the higher educational levels. Over time, schoolwork pressure increased most among girls in the highest educational levels. Explanations and implications for these results are discussed.
Keywords: Ethnicity; chování mladistvých; the Netherlands; lidé; mladiství; školy; studenti; time trends; tracked educational system; stupeň vzdělání; School stress; dítě; Child; Schools; gender; ženské pohlaví; Humans; Students; educational level differences; etnicita; Adolescent Behavior; Educational Status; Female; Adolescent; HBSC